A ‘Very Jewish’ Jesus: Perpetuating the Myth of Superiority - Crossley, James G. (Journal for the study of the historical Jesus, 2013)
This article looks at arguably the most dominant rhetorical move in contemporary historical Jesus scholarship, namely the ‘Jewishness’ of Jesus or a ‘very Jewish’ Jesus, and how this superficially but credibly positive rhetoric subtly maintains the older myth of superiority over against Judaism. This scholarly trend is located in contemporary ideological discourses concerning Israel and Judaism and liberal multiculturalism and is shown to be deeply embedded in scholarly historical practice. Some consideration is also given to the ideological locations of the ‘Judean’ and ‘Jesus the Israelite’ debate.